The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.5688/ajpe6167
|View full text |Cite
|
Sign up to set email alerts
|

Team-Based Learning Experiences of Fourth-Year Pharmacy Students in a South African University

Abstract: Objective. To determine fourth-year pharmacy students' learning experiences with team-based learning (TBL) at a South African university. Methods. A survey composed of biographical data and quantitative questions focusing on student learning experiences was sent to students. There were 183 (91.5%) students who completed the survey. Results. Students had a positive experience with TBL and found it valuable and more worthwhile than traditional lecture methods, regardless of their initial negative perception of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
2
3
0
1
Order By: Relevance
“…We found that TBL provided a good learning experience for our students, almost in totality. While many publications corroborate our data (23,(25)(26)(27)(28)(29), a small, but representative, number report divergent results, describing negative experiences with TBL (30,31). Here, 96% of students got satisfied with TBL sessions, 97% agreed that TBL helped them to learn and 87% approved the use of TBL in other moments in the future.…”
Section: Discussionsupporting
confidence: 71%
“…We found that TBL provided a good learning experience for our students, almost in totality. While many publications corroborate our data (23,(25)(26)(27)(28)(29), a small, but representative, number report divergent results, describing negative experiences with TBL (30,31). Here, 96% of students got satisfied with TBL sessions, 97% agreed that TBL helped them to learn and 87% approved the use of TBL in other moments in the future.…”
Section: Discussionsupporting
confidence: 71%
“…This does not reflect the theory of that TBL becomes an enjoyable and valuable learning tool, and students respond positively after experienced it. TBL favor increased after students learning experience with TBL [3]. This phenomenon could be a result of motivational variations between year two and year three students.…”
Section: Discussionmentioning
confidence: 91%
“…Team-based learning (TBL) has become an increasingly important educational method of a medical curriculum in the last few years [1,2]. It was first introduced by Larry Michaelsen in 1970 within the field of business education [3,4]. Later, TBL found to be suitable for health profession education because of its relevancy as a student-centered learning philosophy [4].…”
Section: Introductionmentioning
confidence: 99%
“…O trabalho em equipe propicia motivação e impacto positivo na aprendizagem e é um bom método para simular atividades que requeiram trabalho em grupo 1,12 . Para esse impacto realmente ter efeito, o grupo deve seguir algumas etapas básicas do aprendizado em equipe, como a formação do grupo, processo de garantia de prontidão, feedback imediato, sequenciamento em sala de aula, resolução de problemas, estrutura motivacional e exercícios de aplicação da equipe 3 .…”
Section: Gráfico 1 Gráfico De Floresta Com Análise Das Frequências Daunclassified